(untitled) (International journal of artificial intelligence, 2025)
The article considers the linguistic analysis of a literary text as a method of studying the specifics of the author's style. The concept of a literary text is clarified, the main aspects and tools of linguistic analysis are described, and the relationship between the system of linguistic means and individual author's stylistic characteristics is revealed. Special attention is paid to genre and language features that influence the formation of a writer's style.